Biotransformation of anthelmintics in nematodes in relation to drug resistance - Ondřej Vosála; Josef Krátký; Petra Matoušková; Nikola Rychlá; Karolína Štěrbová; Lucie Raisová Stuchlíková; Ivan Vokřál; Lenka Skálová (International Journal for Parasitology: Drugs and Drug Resistance)
In all organisms, the biotransformation of xenobiotics to less toxic and more hydrophilic compounds represents an effective defense strategy. In pathogens, the biotransformation of drugs (used for their elimination from the host) may provide undesirable protective effects that could potentially compromise the drug's efficacy. Accordingly, increased drug deactivation via accelerated biotransformation is now considered as one of the mechanisms of drug resistance. The present study summarizes the current knowledge regarding the biotransformation of anthelmintics, specifically drugs used to treat mainly nematodes, a group of parasites that are a significant health concern for humans and animals. The main biotransformation enzymes are introduced and their roles in anthelmintics metabolism in nematodes are discussed with a particular focus on their potential participation in drug resistance. Similarly, the inducibility of biotransformation enzymes with sublethal doses of anthelmintics is presented in view of its potential contribution to drug resistance development. In the conclusion, the main tasks awaiting scientists in this area are outlined.